Seeking Hang Tuah - Muhammad Haji Salleh 1942- (University of Malaya Press, 2020)
Hang Tuah is a culture hero without compare, in Malay Literature and beyond. For more than 500 years he has been present in the oral words, pages of the Hikayat, traditional theatre, poetry, comics and critical discourses, for within his person, he combines the social and moral ideals of Malaysians as well as many other readers in the Malay world. For all these years he has also been present in the Malaysian sub-conscience, because for many, he represents the values and identity of the Malays and Malaysians, the Indonesians, Singaporeans and Bruneians. But as his values and person have travelled the world he has also became a universal man. Prof. Muhammad Haji Salleh has recently transcribed the earliest version of the Hikayat Hang Tuah. However, he has also earlier translated one of its versions into English, a formidable work of not less than 500 pages. Besides, he has studied the narrative and the hero (and his comrades) for not less than 40 years. He is thus eminently qualified to guide us to seek Hang Tuah. Furthermore, for he has also has travelled to the various places purported to be the birthplace and mausoleum of the hero. There is a description of a journey by boat to the Bakung River and the Duyung Village, in the Singkep Island of the Riau Archipelago in Indonesia. In addition he has also written about him and the Hikayat from several perspectives - his origins, youth, principles of leadership, knighthood, ideas of loyalty and rebellion, travels and spaces. Prof. Muhammad is thus exceptionally equipped to help us seek out Hang Tuah, to acquaint us with his origins and journeys, his values, and the principle qualities that have endeared him to the generations. Furthermore, has also traced the contemporary discourse, not only between Hang Tuah and his friend/antagonist, Hang Jebat, but also the relentless oral development of the epic in a sea of stories that ebbs and rises in the secondary and tertiary oralities, and in our academic halls and public spaces.